Analysis of sensitivity patterns for characteristics of magnetotelluric (MT) response functions in inversion. Issue 3 (19th January 2023) - Uhm, Janghwan; Oh, Ju-Won; Min, Dong-Joo; Heo, Junyeong
SUMMARY: Because the magnetotelluric (MT) method uses natural sources, the electric and magnetic fields recorded in the field acquisition are not directly used but usually converted into other MT response functions for interpretation such as inversion. Considering that inversion results are dependent on types of input data, it can be helpful to analyse different characteristics of MT response functions for inversion. In this study, we examine sensitivity patterns of MT response functions used commonly in MT inversion, which are the impedance tensor, apparent resistivity, phase, tipper, effective impedance and phase tensor; and investigate how their sensitivity patterns affect inversion results. We first describe overall tendencies of 3-D sensitivity patterns of the MT response functions, and then classify the MT response functions into six groups based on 2-D sensitivity patterns computed at the surface, which are briefly called 'surface-sensitivity patterns' in this study. The 'diagonal components of the impedance' and 'off-diagonal components of the phase tensor', which have four petals-shaped surface-sensitivity patterns along the diagonal directions, belong to Group 1, and contribute to imaging 3-D subsurface structures from receivers installed evenly at the surface. Group 2 contains the ' xy -components of the impedance, apparent resistivity and phase' and ' yy -component of the phase tensor' whose surface-sensitivity patterns are linear in the y -axis. The ' yx -components of the impedance, apparent resistivity and phase' and ' xx -component of the phase tensor' that have strong linear surface-sensitivity patterns along the x -axis are classified into Group 3. The MT response functions of Groups 2 and 3 are useful for inversion of structures close to 2-D, whose strike extends along the y - and x -axes, respectively. Groups 4 and 5 include the ' x - and y -components of tipper' that possess linearly aligned two petals-shaped surface-sensitivity patterns in the x - and y -axes, respectively. The tipper can be helpful in imaging both 2-D and 3-D structures. The 'effective impedance' belongs to Group 6, whose surface-sensitivity patterns appear as a small circle. The surface-sensitivity patterns allow the effective impedance to have an advantage in interpretation of 1-D structures. By using several MT response functions for specific cases of 1-D, 2-D and 3-D interpretation of MT data, we investigate whether characteristics of the sensitivity patterns are reflected in modelling (simulating field data) and inversion results, and then suggest optimal MT response functions for those cases. In doing so, we show how to utilize the characteristics of the sensitivity patterns in inversion, and recommend the input MT response functions for inversion according to MT exploration situations. Our study provides basic information on similarities and differences of major MT response functions for inversion and insights on which MT response functions are suitable to increase the feasibility of MT inversion for different field situations based on the sensitivity patterns.